2020
DOI: 10.1590/0037-8682-0132-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of arenavirus and hantavirus in indigenous populations from the Caribbean, Colombia

Abstract: Introduction: In Colombia, there is insufficient epidemiological surveillance of zoonotic hemorrhagic viruses. Methods: We performed a sero-epidemiological study in indigenous populations of Wayuü, Kankuamos, and Tuchin communities using Maciel hantavirus and Junin arenavirus antigens for IgG detection by ELISA. Results: IgG antibodies to hantavirus and arenavirus were found in 5/506 (1%) and 2/506 (0.4%) serum samples, respectively. Conclusions: Arenavirus and hantavirus circulate in indigenous populations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…An epidemiological study evaluating two nearby regions, with the same climatic conditions during the same EWs, found different prevalences of 57�1% and 45�7% [25]. This difference in seroprevalence in areas with similar climatic and geographical characteristics is possibly related to several factors, such as population density, sampling type, degree of vector mosquito infestation, sanitary structure of neighborhoods, and commercial activity in the city [10,11,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An epidemiological study evaluating two nearby regions, with the same climatic conditions during the same EWs, found different prevalences of 57�1% and 45�7% [25]. This difference in seroprevalence in areas with similar climatic and geographical characteristics is possibly related to several factors, such as population density, sampling type, degree of vector mosquito infestation, sanitary structure of neighborhoods, and commercial activity in the city [10,11,25].…”
Section: Discussionmentioning
confidence: 99%
“…The Northeast Region of Brazil, where European colonization began, is home to Indigenous peoples with diverse ethnicities and traditions [10]. However, very few studies have evaluated the impact of new epidemics on Indigenous communities [11].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Furthermore, one species of hantavirus can infect multiple rodent hosts, which is similar to the observed Mammarenavirus dynamics in this study [ 45 ]. Co-infections between Arenaviridae and Hantaviridae are rare, but can occur naturally within shared rodent host species, as shown by the seroprevalence of Maciel virus and Junin virus in Colombia [ 49 ]. There have also been documented co-infections between Old World Mammarenaviruses and Orthohantaviruses , as shown by the presence of both lymphocytic choriomeningitis virus (LCMV) antibodies and Orthohantavirus antibodies in rodents from Italy and Spain [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence found for Mammarenavirus of the Tacaribe complex (1,64%) was comparable to that found in other studies carried out in human population in the country. Percentages between 0.5% and 3.1% had been described in indigenous populations and inhabitants of rural areas [3,5], indicating the circulation of these viruses between people who live in areas far from cities and who have contact with wild rodents such as those belonging to the Cricetidae family and the Sigmodontine subfamily. It should be clarified that although the seroprevalence values are low, they are similar to those found in other regions of the continent where important outbreaks of disease have occurred in humans [17].…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, no cases of Mammarenavirus fever have been reported due the absence of appropriated diagnostic infrastructure and its symptoms could be confused with those produce by other endemic agents as dengue, malaria, among others. However, previous studies have shown the circulation of Mammarenavirus in both rodents and humans [2][3][4][5]. Additionally, the high diversity of rodent species found in Colombia and the results of previous study that identified seropositive Zygodontomys brevicauda reservoirs of Guaranito virus, indicates the potential presentation of human cases in the territory [4,6].…”
Section: Introductionmentioning
confidence: 99%